FEATURES OF THE USE OF INDUCTION CRUCIBLE FURNACES FOR MELTING METALS - Khaydarov Ahmadali Kambarovich; Karimov Bohodir Yusufjonovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents the classification of electrotechnological and electrothermal installations, in particular, induction crucible furnaces. A retrospective analysis of the development of electric power engineering is given. The principle of operation, design and purpose of induction crucible furnaces are considered.